1996
DOI: 10.2494/photopolymer.9.601
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-Effect of Chemically Amplified Resist.

Abstract: SiN, Bare Si, and Si02 substrate-effects in chemically amplified (CA) resist have been investigated by surface analysis and evaluating the pattern profile of CA negative tone resist. It is considered that substrate-effects are distinguished from adhesion, optics and substrate components. It is found that the undercut profile of negative tone resist on SiN substrate can not be due to adhesion and optics. Fine profile can be replicated on SiN substrate treated with oxygen plasma optimized condition. Undercut pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…There was no significant difference in reflectivity between an SiN thickness of 70 nm and 100 nm. BARC also worked to prevent the expected tapered profile often observed at the bottom of a resist fabricated on some inorganic films [15][16]. Therefore, we applied DUV42 (at a thickness of 30 nm), which showed good compatibility with F-resist A-C and a relatively high etching rate, as an organic BARC on SiN.…”
Section: Resist Processingmentioning
confidence: 99%
“…There was no significant difference in reflectivity between an SiN thickness of 70 nm and 100 nm. BARC also worked to prevent the expected tapered profile often observed at the bottom of a resist fabricated on some inorganic films [15][16]. Therefore, we applied DUV42 (at a thickness of 30 nm), which showed good compatibility with F-resist A-C and a relatively high etching rate, as an organic BARC on SiN.…”
Section: Resist Processingmentioning
confidence: 99%
“…are catalyst scavengers in chemically amplified resists [4,7]. To evaporate H2O and NH3, we baked the substrate at 500 t in a vacuum (vacuum pressure was less than 10E-5 torr).…”
Section: Effect Of High-temperature Baking Treatment On Sionmentioning
confidence: 99%
“…It was reported that the resist footing in negative chemically amplified resist on SiN derived from roughness [4]. We measured root mean roughness (from AFM) for samples ( table 1).…”
Section: Effect Of Oxygen Plasma Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It is apparent that factors, such as profile, exposure latitude and CD reliability are important criteria for using the CA resist in device mass-production. But these are not near completion because the CA resist has some problems due to atmospheric or substrate contamination [2][3][4]. Many empirical and laborious approaches to improve the contamination susceptibility of resist processes have been attempted, such as chemical filters for improving the environmental air [5-b], an overcoat film for sealing from environmental contamination [7][8], and modification of the resist itself [9][10].…”
Section: Introductionmentioning
confidence: 99%